Using R for digital soil mapping - Malone, Brendan P.; Minasny, Budiman; McBratney, A. B. (Springer Nature, 2017)
This book describes and provides many detailed examples of implementing Digital Soil Mapping (DSM) using R. The work adheres to Digital Soil Mapping theory, and presents a strong focus on how to apply it. DSM exercises are also included and cover procedures for handling and manipulating soil and spatial data in R. The book also introduces the basic concepts and practices for building spatial soil prediction functions, and then ultimately producing digital soil maps.
Keywords: Digital soil mapping.; R (Computer program language); elektronické knihy; electronic books